Clonal integration of the invasive plant Wedelia trilobata (L.) Hitch in stress of flooding type combination (International Journal of Plant Biology, 2019)
The clonal invasion of Wedelia trilobata (L.) Hitchhas spread to riverside and edges of mangrove areas, which leads to the formation of flooding-stressed areas such as waterlogged and submergence. This study purpose to investigate the clonal integration mechanism of W. trilobata in stress of flooding type combination. This study was conducted in greenhouse with four combinations of flooding treatment on mother ramet (MR) and daughter ramet (DR) for 25 days. Several parameters were measured are shoot growth, relative growth rate (RGR), biomass, biomass allocation, adventitious root growth, and lenticel hypertrophy. The highest clonal performance was observed for the combination of field capacity (MR)-waterlogged( DR). The lowest performance was observed for the combination of waterlogged (MR)-submergence (DR). There were decreases in the shoot growth, RGR, and biomass allocation in mother ramet. However, adventitious root growth and lenticel hypertrophy increased in daughter ramet. The increase of flooding pressure suppresses the performance of clonal plants. Clonal integration buffered clonal plants by improving the performance of daughter ramet in the combination of flooding type. The clonal integration has facilitated W. trilobata invasion in inundated areas.